Transformasi akuntansi dari manual ke otomatisasi - Tushofiyah, Sa’ida (Maliki Interdisciplinary Journal, 2024)
This research aims to find out how accounting transformation from manual to automation. In this research, researchers collect data or information related to accounting transformation from manual to automation. The results showed that in this transformation, automation increases operational efficiency compared to manuals that take longer. The example is in accelerating the process of recording and financial reporting. Technology also plays an active role in supporting accounting transformation to automation. However, in this case there are also obstacles such as unsupportive policies or rigid regulations that can hinder new technological innovations in accounting. The main impact of this transformation is a shift in focus from administrative tasks to a more strategic role. Accountants are expected to not only present financial statements, but also analyze.